KNOWLEDGE CREATION AND INNOVATIVE BEHAVIOR - Setiawan, Yana; Yuniarsih, Tjutju; Suwatno, Suwatno; Ahman, Eeng (Faculty of Economics and Business Education Indonesia University of Education, 2018)
The current business development is entering the industry era 4.0. To anticipate the development of the industry era 4.0, employee performance aspect in human resource management becomes very important. Problems in this research is the low innovative behavior of employees described by the phenomenon of decline and increase performance of employee performance PT. Perkebunan Nusantara VIII (PTPN VIII) in Industrial era 4.0 in Indonesia. If the human resource problem is not addressed immediately, it will have an impact on the achievement of corporate management objectives which in turn also affect the performance, productivity, competitiveness and sustainability of the company. The purpose of this study is to describe and analyze employee perceptions on (1) the effectiveness of knowledge creation and the level of innovative behavior (2) Effect of the effectiveness of knowledge creation on the level of innovative behavior. The research method used a quantitative approach that is descriptive and verification through descriptive survey and explanatory survey. Respondents and research population are employees of PTPN VIII as many as 3999 people, with sample size of 364 people. The data analysis technique used Structural Equation Modeling (SEM) with SPSS and AMOS 24 software tools. The findings of the research show that (1) Knowledge creation is in effective category and innovative behavior is in high category. (2) Knowledge creation has a positive and significant effect on innovative behavior